VOLATILE FLAVOUR COMPONENTS OF ALLTUM SATIVUM ESSENTIAL OIL FROM PAKI TAN: ?Short Communications (Biological Sciences - PJSIR, 1998)
Nitrogen was used as a carrier gas with a flow velocity of1-2 ml min' and split ratio I: 100 and sample size 0.1 Ill.The column temperature was programmed at 70°C Ior 4 min.with 4°C min-I rise to 220°C, while dector and injectortemperatures of 300°C and 250°C respectively were used,Percentage composition of individual components wascalculated on the basis of peak area using a SchimadzuC-R4A chr matopac electronic integrator.